Analysis of plant nutrient elements of soil in Pokhara - Subedi, Thaneshwar (Himalayan Biodiversity, 2018)
The study was carried out to analyse plant nutrient elements present in soil samples from different part of Pokhara metropolitan city and to compare them with standard recommended values. The plant nutrient elements of soil samples nitrogen, phosphorus, potash, zinc, iron, copper, and boron were analyzed by using specific techniques. The PH was analysed by PH meter, organic matter by gravimetric method, nitrogen by Kjeldal method and phosphorus by Olsen’s method (1954) of analysis. Similarly, the amount of zinc, iron and copper were determined by chemical method, potassium by flame photometer method, and boron by using a spectrophotometer. The essential macronutrients nitrogen, phosphorus and potash remained within the permissible limit for most of the samples. The essential micronutrients zinc, copper and boron in four samples were within the acceptable range. The content of iron was higher than that required as an essential crop nutrient. The observed values of plant nutrient elements expressed that the sampling area could be used for agricultural cultivation and production.